The diagram for phyllotactic series - Joanna Szymanowska-Pułka; Wiesław Włoch (Acta Societatis Botanicorum Poloniae, 2014)
Many authors studying phyllotaxis in various plant species have reported the occurrence of many different numbers of contact parastichy pairs that are members of different Fibonacci-like series. On the basis of these reports a diagram was constructed in which any theoretically possible series was represented by the two first members of a given series.